Symbolic Significance in the Design of Contemporary Sculptures in the Kingdom of Saudi Arabia - Khasawneh, Fuad Eyad (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to uncover the symbolic meanings in their sculptural compositions and the influence of the artists' self-expression on those meanings. It also aimed to investigate the concept of sculptural symbolism and contemporary sculpture in the Kingdom of Saudi Arabia. Methodology: The researcher adopted a descriptive-analytical approach and provided an analysis of selected research samples. The study's results yielded several findings. Results: The personal experiences of Saudi sculptors primarily informed the derivation and appropriation of symbolic meaning from heritage and local elements, utilized in the design of sculptural works in Saudi Arabia. The researcher discussed these results in relation to findings from related studies. Conclusion: The study concluded that the art of sculpture and its association with Saudi identity in contemporary times are still evolving. It suggested that the design of Saudi sculptural works could be viewed as a contemporary aesthetic research case with symbolic significance.